Meningkatan Hasil Belajar IPS melalui Model Pembelajaran Problem Based Learning Berbantuan Media Gambar Siswa Kelas VI.B SD Negeri Model Mataram - Utami, Luh Made Diah (ARZUSIN, 2022)
The aim of this research is; 1) To find out the application of the problem based learning model with the aid of image media to the social studies material for students in class VI.B of the Mataram Model State Elementary School in the Odd Semester of the 2021/2022 Academic Year; 2) To find out the improvement of social studies learning outcomes through a problem-based learning model assisted by image media for Class VI.B students of the Mataram Model State Elementary School in the Odd Semester of the 2021/2022 Academic Year. This research is a Classroom Action Research (CAR), using two cycles through the stages of planning, implementing action, observing, and reflecting. The subjects in this study were class VI.B students of SD Negeri Model Mataram for the academic year 2021/2022 with a total of 18 students, consisting of 10 male students and 8 female students. The results of this study indicate that; The application of the Problem Based Learning model assisted by picture media in social studies learning can improve student learning outcomes when teaching and learning activities take place, that of the number of students, namely 18 people, whose scores are equal to or more than the KKM are 18 people, and if the percentage is 100%. This shows an increase from the initial conditions and the first cycle, namely from the number of students who completed as many as 13 people (72.22%) then to 15 people (83.33%) and increased again to 18 people (100%); The application of the Problem Based Learning model in social studies learning can improve student learning activities. The score of students' ability in social studies learning using the Problem Based Learning model in class VI.B of the Mataram Model State Elementary School during the first cycle to the second cycle continued to increase. In the first cycle, the score of students' improvement in learning was 25.00%. In the implementation of the second cycle the score increased by 17.50%, an increase of 42.50 points. While the teacher's ability score in implementing social studies learning using the Problem Based Learning model in class VI.B SD Negeri Mataram Model during the implementation of the first cycle to the second cycle continued to increase. In the first cycle the teacher's ability to carry out learning is 78.67%. In the second cycle the teacher's ability to carry out learning increased by 93.33%. In the implementation of the second cycle the teacher's ability to carry out learning has increased by 14.66 points.